A high-precision chronology for the rapid extinction of New Zealand moa (Aves, Dinornithiformes) - Perry, George L.W.; Wheeler, Andrew B.; Wood, Jamie R.; Wilmshurst, Janet M. (Quaternary science reviews, 2014)
Megafaunal extinction followed the prehistoric human settlement of islands across the globe, but the exact duration and dynamics of the extinction processes are difficult to determine. The New Zealand moa (Aves, Dinornithiformes) are a prime example, where, despite an extensive fossil and archaeological record, debate continues about their extinction chronology and how extinction timings varied among regions and species. We apply probabilistic sightings methods to 111 high-quality radiocarbon dates (from a pool of 653 dates) on moa remains from natural and archaeological sites to provide a high-resolution spatio-temporal chronology of moa extinction. We interpret this alongside an estimated time for the onset of hunting pressure, obtained by applying the same methods to the most reliable proxies for initial human settlement of New Zealand: coprolites of and seeds gnawed by the commensal Pacific rat (Rattus exulans). By comparing local and national extinction times, we discriminate between the point at which hunting stopped (economic extinction) and the total extinction of moa (ca 150 and 200 years after settlement, respectively). Extinction occurred contemporaneously at sites separated by hundreds of kilometres. There was little difference between the extinction times of the smallest (20–50 kg) and largest (200+ kg) moa species. Our results demonstrate how rapidly megafauna were exterminated from even large, topographically- and ecologically-diverse islands such as New Zealand, and highlight the fragility of such ecosystems in the face of human impacts. •We evaluate the extinction pattern in space and time of moa across New Zealand.•The extinction event lasted 1–2 centuries and was geographically synchronous.•Moa taxa with different body-mass suffered extinction at the same time.•The demographic traits of moa made them vulnerable to even moderate hunting pressure.